Ethnomathematics comics of Al-Akbar Mosque: Enhancing elementary students' understanding of geometric shapes - Oktavia, Aulia Ika Aulia; Yustitia, Via; Hadi, Susilo; Wijaya, Tommy Tanu (Universitas Sarjanawiyata Tamansiswa, 2025)
Learning is evolving rapidly in the 21st century, as evidenced by advancements in science and technology (IPTEK), including the use of comics as a medium for learning mathematics. The incorporation of ethnomathematics comics based on the architectural features of Masjid Al-Akbar Surabaya serves as an innovative learning tool to address issues such as unengaging media and students’ reluctance to learn mathematics. This study aims to: (1) examine the process of developing ethnomathematics comics about the Al-Akbar Mosque of Surabaya to help elementary school students recognize the names and characteristics of geometric structures; (2) assess the feasibility of these comics as a learning medium; and (3) analyze teachers' and students' responses to their implementation in the classroom. This study employs a research and development (R&D) approach using the ADDIE development model, which consists of four stages: analysis, design, development, and implementation. Data collection methods include documentation, surveys, observations, interviews, and literature reviews, while data analysis combines qualitative descriptive and quantitative techniques based on expert validation and Likert-scale responses. The results indicate that (1) the three initial stages of the research process—analysis, design, and development—were successfully carried out according to the established framework; (2) validation data from material experts, linguists, and learning media specialists rated the comics as